Implant-forming polymeric 19F MRI-tracer with tunable dissolution - Kolouchova, Kristyna; Jirak, Daniel; Groborz, Ondrej; Sedlacek, Ondrej; Ziolkowska, Natalia; Vit, Martin; Sticova, Eva; Galisova, Andrea; Svec, Pavel; Trousil, Jiri; Hajek, Milan; Hruby, Martin (Journal of controlled release, 2020)
Magnetic resonance imaging (MRI) using 19F-based tracers has emerged as a promising multi-purpose noninvasive diagnostic tool and its application requires the use of various 19F-based tracers for the intended diagnostic purpose. In this study, we report a series of double-stimuli-responsive polymers for use as injectable implants, which were designed to form implants under physiological conditions, and to subsequently dissolve with different dissolution rates (t1/2 ranges from 30 to more than 250 days). Our polymers contain a high concentration of fluorine atoms, providing remarkable signal detectability, and both a hydrophilic monomer and a pH-responsive monomer that alter the biodistribution properties of the implant. The implant location and dissolution were observed using 19F MRI, which allows the anatomic extent of the implant to be monitored. The dissolution kinetics and biocompatibility of these materials were thoroughly analyzed. No sign of toxicity in vitro or in vivo or pathology in vivo was observed, even in chronic administration. The clinical applicability of our polymers was further confirmed via imaging of a rat model by employing an instrument currently used in human medicine.
Keywords: polymery; (19)F magnetic resonance imaging; krysa rodu Rattus; Animals; Magnetic Resonance Imaging; Tunable dissolution; Polymers; Fluorine; zvířata; fluor; magnetická rezonanční tomografie; Double-stimuli responsivity; Tissue Distribution; Polymer implant; Solubility; Rats; rozpustnost; tkáňová distribuce